2016
DOI: 10.4103/2152-7806.178135
|View full text |Cite
|
Sign up to set email alerts
|

Unusual coexistence of an epidermoid cyst with an atypical meningioma: Case report and review of the literature

Abstract: Background:Coexistence of multiple primary intracranial tumors of different cell types has rarely been documented; the association of a meningioma and a glioma has been reported as the most common combination. Hereby, we report an unusual case of a temporal epidermoid cyst coexisting with an atypical meningioma.Case Presentation:A 37-year-old male presented with progressive symptoms of raised intracranial progression with progressive loss of vision without any neurological deficit. On admission, magnetic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Thomalske and Galow were reported meningioma and cerebellopontine angle epidermoid cyst in 1975 5 . In 1979, Frazer and Victoratos 6 reported a co-existing epidermoid cyst and meningioma developed after cranial radiotherapy Karekezi et al reported a patient with right frontal lobe meningioma and right temporal lobe epidermoid cyst in 2016 7 . While the anatomical location of both tumors is different in most cases of meningiomas and epidermoid cysts reported in the literature, Kumar et al reported the association of meningioma and epidermoid cyst located in the same localization 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thomalske and Galow were reported meningioma and cerebellopontine angle epidermoid cyst in 1975 5 . In 1979, Frazer and Victoratos 6 reported a co-existing epidermoid cyst and meningioma developed after cranial radiotherapy Karekezi et al reported a patient with right frontal lobe meningioma and right temporal lobe epidermoid cyst in 2016 7 . While the anatomical location of both tumors is different in most cases of meningiomas and epidermoid cysts reported in the literature, Kumar et al reported the association of meningioma and epidermoid cyst located in the same localization 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Epidermoid cysts are tumors of embryological origin, and studies on whether they affect the development of meningioma are limited. Karekezi et al stated that according to their theory, the cerebrospinal fluid (CSF) circulating around and under the arachnoid membrane of the epidermoid cyst might be an effective factor in the development of meningioma by stimulating tumor cell growth through irrigation of neighboring regions 7 . It has been suggested that meningiomas secrete EGF and EGF secretion, and local paracrine stimulation may play a role in the development of epidermoid cysts 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple primary intracranial tumors of different cell types were observed only in patients with neurofibromatosis type 2, a finding that is rare in other patients. The most common comorbidity of various types of cancer is meningioma with glioma [6] . When performing the differential diagnosis of rapidly growing skull lesions, it is important to be aware of impingement tumors to ensure optimal treatment.…”
Section: Introductionmentioning
confidence: 99%